2021
DOI: 10.1111/apm.13159
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency in K14E7HPV expressing transgenic mice facilitates the formation of malignant cervical lesions

Abstract: Infection with high-risk human papillomavirus (HR-HPV) is the main cause of cervical cancer (CC), but viral infection alone does not guarantee the development of this malignancy. Indeed, deficiencies of dietary micronutrients could favor cervical cancer development in individuals that harbor HR-HPV infections. The status of retinoid levels, natural and synthetic derivatives of vitamin A, is important in maintaining cellular differentiation of the cervical epithelium. Moreover, many studies show a link between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In fact, retinoids have the ability to inhibit cell proliferation through the tumor suppressor RARβ. [17][18][19][20] According to our observations, a single E 2 stimulus was enough to decrease the levels of apoptosis in both the FvB and K14E7 mice. Previous studies have demonstrated that E 2 has the ability to inhibit apoptosis mediated by estrogen receptors.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In fact, retinoids have the ability to inhibit cell proliferation through the tumor suppressor RARβ. [17][18][19][20] According to our observations, a single E 2 stimulus was enough to decrease the levels of apoptosis in both the FvB and K14E7 mice. Previous studies have demonstrated that E 2 has the ability to inhibit apoptosis mediated by estrogen receptors.…”
Section: Discussionmentioning
confidence: 52%
“…Among the possible metabolites responsible for the antiproliferative activity of ELj, is retinol, whose intake has been proposed to reduce the risk of CC since it has been shown that this molecule is capable of regulating multiple cellular processes since the cervical epithelium is highly sensitive to Vitamin A. In fact, retinoids have the ability to inhibit cell proliferation through the tumor suppressor RARβ 17‐20 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, researchers also found that the chronic stress and diurnal cortisol also play an important role in HR‐HPV infection and HPV‐associated cervical carcinogenesis 295 . Furthermore, dietary factors also appear to play an important role in the animal experiment and human clinical research and both show that diets with low antioxidants (vitamin A, B2, E, and folate) are more likely to develop HPV infections 296,297 …”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%
“… 295 Furthermore, dietary factors also appear to play an important role in the animal experiment and human clinical research and both show that diets with low antioxidants (vitamin A, B2, E, and folate) are more likely to develop HPV infections. 296 , 297 …”
Section: Hpv and Its Pathogenesismentioning
confidence: 99%
“…Another therapeutic resource for HPV neoplasms is the systemic administration of retinoids such as vitamin A ( Oren-Shabtai et al, 2021 ), due to the retinoid deficiency is associated with the methylation of the retinoic acid receptor β 2 (RARβ2), a tumor suppressor. In a transgenic mouse model, it was shown that the expression of HPV E7 and the lack of dietary retinoids induce proliferation, hyperkeratinization, development of precursor lesions, and cancer in situ ( Ocadiz-Delgado et al, 2021 ).…”
Section: Epigenetic Therapy and Chemopreventionmentioning
confidence: 99%